Early detection and management of ganoderma basal stem rot disease: a special report from Sabah - Chong, Khim Phin; Arnnyitte Alexander; Syahriel Abdullah (e-VIBS, Faculty of Science and Natural Resources, 2016)
Basal Stem Rot (BSR) disease caused by Ganoderma spp. is the most devastating disease of oil palm in Southeast Asia. This paper discusses sustainable approaches in managing BSR disease particularly on early detection and control of Ganoderma with some examples from oil palm estates in Sabah. New detection methods such as ergosterol analysis and Ganoderma signature via Fourier Transform Infrared Spectroscopy (FTIR) are emphasized. Latest disease control methods with great potentials such as combination of biological control agents (BCAs), enhancing defense mechanism of oil palm through enviro-friendly approach, potential biomarkers for selection of resistant breeding materials and utilization of eco-friendly fungicide were also discussed.